The Effects of Social Skills Interventions for Students With EBD and ASD: A Single-Case Meta-Analysis. Issue 5 (September 2020) - Hutchins, Nancy S.; Burke, Mack D.; Bowman-Perrott, Lisa; Tarlow, Kevin R.; Hatton, Heather
Social skills interventions are critical for promoting social, emotional, and behavioral competence for students with or at risk of emotional and behavioral disorders (EBD) and autism spectrum disorders (ASD). This single-case meta-analysis examined the effects of social skills interventions (SSIs) for students with EBD and ASD. Effect sizes were calculated for 78 cases across 25 included studies using a nonparametric effect size, Baseline Corrected Tau. The overall weighted mean effect size of 0.54 suggested a moderate effect across the 25 studies. The overall weighted mean effects for studies reporting maintenance and generalization data were 0.68 and 0.37, respectively. Potential moderators examined (disability, intervention design, intervention delivery, methodological quality) were not significant. As such, they did not moderate the outcomes for participants. We conducted a post hoc analysis and hypothesized that between-study differences may be more meaningful than the similarities shared by participants in the same moderator groups. Implications are discussed on using SSIs to address the social, emotional, and behavioral challenges of students with or at risk of EBD and ASD.